Expansion of chronic lesions is linked to disease progression in relapsing-remitting multiple sclerosis patients - Klistorner, Samuel; Barnett, Michael H; Yiannikas, Con; Barton, Joshua; Parratt, John; You, Yuyi; Graham, Stuart L; Klistorner, Alexander (Multiple sclerosis, 2021)
Slow-burning inflammation is putatively associated with lesion expansion and leads to progressive loss of axons and disability worsening.BACKGROUNDSlow-burning inflammation is putatively associated with lesion expansion and leads to progressive loss of axons and disability worsening.To investigate the incidence and extent of chronic white matter lesion expansion in relapsing-remitting multiple sclerosis (RRMS) patients and to evaluate its relationship with biomarkers of disease progression.OBJECTIVETo investigate the incidence and extent of chronic white matter lesion expansion in relapsing-remitting multiple sclerosis (RRMS) patients and to evaluate its relationship with biomarkers of disease progression.Pre- and post-gadolinium T1, fluid-attenuated inversion recovery (FLAIR) and diffusion tensor images were acquired from 33 patients. Lesional activity were analysed between baseline and 48 months using custom-designed software.METHODSPre- and post-gadolinium T1, fluid-attenuated inversion recovery (FLAIR) and diffusion tensor images were acquired from 33 patients. Lesional activity were analysed between baseline and 48 months using custom-designed software.A total of 569 lesions were identified as chronic at baseline, of which 261 were expanding, 236 were stable and 72 were shrinking. In addition, 139 new lesions (both confluent and free-standing) were observed. Chronic lesion expansion was associated with patient's age and accounted for the bulk (67.3%) of total brain lesion volume increase, while only 32.7% was attributable to new lesion formation. Change in chronic lesion volume correlated with the rate of brain atrophy (r = -0.57, p = 0.001), change of Expanded Disability Status Scale (EDSS; r = 0.38, p = 0.03) and an increase of isotropic diffusivity inside the lesions (r = 0.75, p < 0.001).RESULTSA total of 569 lesions were identified as chronic at baseline, of which 261 were expanding, 236 were stable and 72 were shrinking. In addition, 139 new lesions (both confluent and free-standing) were observed. Chronic lesion expansion was associated with patient's age and accounted for the bulk (67.3%) of total brain lesion volume increase, while only 32.7% was attributable to new lesion formation. Change in chronic lesion volume correlated with the rate of brain atrophy (r = -0.57, p = 0.001), change of Expanded Disability Status Scale (EDSS; r = 0.38, p = 0.03) and an increase of isotropic diffusivity inside the lesions (r = 0.75, p < 0.001).Expansion of chronic lesions in RRMS patients is the primary determinant of increased T2 total lesion load. It significantly contributes to disease progression and partially driving axonal loss inside the lesions and brain damage outside of lesional tissue.CONCLUSIONExpansion of chronic lesions in RRMS patients is the primary determinant of increased T2 total lesion load. It significantly contributes to disease progression and partially driving axonal loss inside the lesions and brain damage outside of lesional tissue.